PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK MENGGUNAKAN GEOGEBRA CLASSROOM PADA MATERI PROGRAM LINEAR UNTUK MENINGKATKAN KEMAMPUAN REPRESENTASI MATEMATIS PESERTA DIDIK - Nadya Amalia (Departemen Matematika, 2021)
The purpose of this research is to develop a valid and practical student worksheets using the geogebra classroom on linear program topics. This research used the Plomp model that consist the three stage, which are preliminary research, prototyping stage, and assessment phase. The data in this research is derived from interviews, observations, and questionnaires. The data from interviews and observations are analyzed by descriptive analysis methods, and the data from questionnaire is analyzed by descriptive statistics. The results of this study are (1) the student worksheets developed is in a very valid category with a validity value of 88.83% and (2) the student worksheets can be used easily by students, with a practicality value of 85.87% with a very practical category. Research results can conclude that the student worksheets using the geogebra classroom can be used in the mathematics learning process at class. Keywords ⸻ Student Worksheets, Geogebra Classroom, Linear Program, mathematical Representation Skills